A PARAMETRIC STUDY OF CODE-BASED PERFORMANCE LIMITS FOR WIDE BEAMS (Advances in Civil and Architectural Engineering, 2014)
In this study, we compared the performance limits of building codes and assessed whether these limits could be applied to wide beams. We performed a parametric study, investigating the longitudinal reinforcement ratio, beam width, steel class, and type and spacing of the transverse reinforcement. We obtained the following results from these analyses: Increasing the longitudinal reinforcement ratio reduced the deformation limit corresponding to code-based performance limits. Changing the confinement properties significantly affected the TEC 2007 and ASCE/SEI 41 limits. The performance limits defined by EC8 and ASCE/SEI 41 had similar corresponding plastic deformations, lower than those corresponding to the TEC 2007 strain-based damage limits.The results show that assessing the performance of wide beams by using the performance limits from differentcodes could produce contradictory results.